2021
DOI: 10.1007/s10750-020-04504-7
|View full text |Cite
|
Sign up to set email alerts
|

Abiotic factors driving cyanobacterial biomass and composition under perennial bloom conditions in tropical latitudes

Abstract: While warming and eutrophication have increased the frequency and magnitude of harmful cyanobacterial blooms globally, the scenario for many eutrophic tropical freshwaters is a perennial year-round bloom. Yet, the drivers of persistent blooms are less understood when conditions such as light, temperature, and nutrients favor cyanobacteria growth year-round, and especially in regions facing recurrent periods of drought. In order to understand the drivers of cyanobacteria dominance, we assessed the abiotic condi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 107 publications
(161 reference statements)
3
16
0
Order By: Relevance
“…It has been reported that environmental factors such as light, temperature, and nutrients have an important in uence on the production of cyanotoxins, and that the consequences may be aggravated by climatic changes (Piccini et al 2011;Paerl & Paul 2012;Antunes et al 2015;Huisman et al 2018;Pham et al 2020,Vanderley et al 2021. Melo et al (2019) identi ed high concentrations of TN (484.66 ± 215.16 µg L -1 ) in the Itupararanga reservoir during the same period as this study, reporting that the primary productivity of the reservoir was limited by phosphorus.…”
Section: Discussionsupporting
confidence: 67%
See 2 more Smart Citations
“…It has been reported that environmental factors such as light, temperature, and nutrients have an important in uence on the production of cyanotoxins, and that the consequences may be aggravated by climatic changes (Piccini et al 2011;Paerl & Paul 2012;Antunes et al 2015;Huisman et al 2018;Pham et al 2020,Vanderley et al 2021. Melo et al (2019) identi ed high concentrations of TN (484.66 ± 215.16 µg L -1 ) in the Itupararanga reservoir during the same period as this study, reporting that the primary productivity of the reservoir was limited by phosphorus.…”
Section: Discussionsupporting
confidence: 67%
“…In the present study, although the cyanobacteria biomass decreased at points where thermal strati cation occurred, R. raciborskii and other species that also have aerotopes (D. solitarium, P. isothrix, and A. gracile) were abundant. Furthermore, changes related to the availability of light, due to reduced water transparency, can have a signi cant in uence on regulation of the dominance of cyanobacteria genera throughout the year (Vanderley et al 2021).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that environmental factors such as light, temperature, and nutrients have an important in uence on the production of cyanotoxins, and that the consequences may be aggravated by climatic changes (Piccini et al 2011;Paerl & Paul 2012;Antunes et al 2015;Huisman et al 2018;Pham et al 2020,Vanderley et al 2021. Melo et al (2019) identi ed high concentrations of ) in the Itupararanga reservoir during the same period as this study, reporting that the primary productivity of the reservoir was limited by phosphorus.…”
Section: Discussionsupporting
confidence: 63%
“…In this sense, studies indicate that the semiarid region has already shown symptoms of intensification of eutrophication due to these extreme drought events, increasing the concentration of nutrients, conductivity, solids and algal biomass (Brasil et al, 2016;Costa et al, 2016;Figueiredo & Becker, 2018;Rocha et al, 2018). Furthermore, the decrease in water volume in these dry periods favors the blooms of potentially toxic cyanobacteria (Bouvy et al, 1999;Costa et al, 2019, Medeiros et al, 2015, Vanderley et al, 2021.…”
Section: Introductionmentioning
confidence: 99%